Algumas considerações e entraves ao exercício da profissão de arquitecto no Norte de Portugal no século XVIII
The application of quantitative and statistical methodology to a database on a survey of artists related with architecture who worked in Braga between 1680 and 1800 allowed us to achieve some pertinent conclusions regarding the artistic culture for the period in analysis.